Chapter Una città, il viaggio, le frontiere, un'identità letteraria - Guagnini, Elvio (Biblioteca di Studi di Filologia Moderna, 2021)
Magris had a deep relationship with his hometown Trieste, while feeling the need to distance himself from it through his travels. Travelling is a metaphor for life; it is a weave between the will for conservation and innovation, as well as research. These issues emerge in significant narrative pages such as Non luogo a procedere (2015), which is a lucid and disenchanted consideration of the history of the city, moved by a strong ethical charge, and Tempo curvo a Krems (2019), which is a profound synthesis of the many aspects of Magris' fictional and critical work.